Decolonizing psychological science: introduction to the special thematic section - Adams, Glenn (2015)
Moved by mounting concerns about ongoing forms of multiple oppression (including racialized violence, economic injustice, unsustainable over-development, and ecological damage), we proposed a special thematic section and issued a call for papers devoted to the topic of "decolonizing psychological science". In this introduction to the special section, we first discuss two perspectives—liberation psychology and cultural psychology—that have informed our approach to the topic. We then discuss manifestations of coloniality in psychological science and describe three approaches to decolonization—indigenization, accompaniment, and denaturalization—that emerge from contributions to the special section. We conclude with an invitation to readers to submit their own original contributions to an ongoing effort to create an online collection of digitally linked articles on the topic of decolonizing psychological science.